Reference line-pair values of panoramic radiographs using an arch-form phantom stand to assess clinical image quality - Choi, Da-Hye (Korean Academy of Oral and Maxillofacial Radiology, 2013)
PURPOSE: This study was performed to suggest reference line-pair values of panoramic images with clinically desirable qualities using an arch-form phantom stand. MATERIALS AND METHODS: The line-pair test phantom was chosen. A real skull model was selected for setting the arch-form model of the phantom stand. The phantom stand had slits in four regions (incisor, premolar, molar, TMJ). Four raw images of the test phantom in each region and one raw image of the real skull were converted into 50 test phantom images and 50 skull phantom images with various line-pair values. 50 post-processed real skull phantom images were divided into 4 groups and were randomly submitted to 14 evaluators. Image quality was graded on a 4 point scale (1. good, 2. normal, 3. poor but interpretable, and 4. not interpretable). The reference line pair was determined as the first line-pair value scored less than 2 points. RESULT: The mean scores tended to decrease as the line-pair values increased. The reference line-pair values were 3.19 LP/mm in the incisor, 2.32 LP/mm in the premolar and TMJ, and 1.88 LP/mm in the molar region. CONCLUSION: Image quality evaluation methods and criteria should be able to assess various regions considering the characteristics of panoramic systems. This study suggested overall and regional reference line-pair values and established a set of standard values for them.